Advanced Maternal Age and Low Birth Weight in Primigravid Births - Junus, Kezia Adelize Aurelia; Ekowati, Ana Lucia; Soegiarto, Bertha; Setiawan, Andy (Journal of Maternal and Child Health, 2023)
Background: The number of women who delay pregnancy is increasing. Advanced Maternal Age/ AMA (pregnancies in women aged 35 years or older) have increased risks of complications, such as low birth weight/LBW (up to 1.59 times). The aim of this study is to know the association between AMA with LBW in primigravid births.Subjects and Method: This descriptive and analytical, cross sectional research consists of 169 primigravid births in Atma Jaya Hospital Jakarta, collected with a total sampling method for births between February 2016 to September 2021 meeting inclusion criteria. Independent variable included primigravid maternal age and dependent variable included birth weight. Prematurity was used as a dependent variable and an independent variable in two separate analyses. Characteristics of data are described, and analyses were done with the Fisher’s exact test for the associations between primigravid AMA and LBW, , between primigravid AMA and prematurity, and between primigravid prematurity and LBW Spearman’s correlation test was done for the correlation between primigravid maternal age and birth weight. Results: The proportions of women with higher education and maternal diseases are more elevated in AMA. LBW prevalence is 14.79%. The proportion of LBW is higher in AMA (OR=2.045; CI 95% 0.513 to 8.147), with statistically insignificant association (p=0.253). The correlation between maternal age and birth weight is insignificant (p=0.113). AMA has insignificantly higher odds for prematurity (OR=1.139; CI 95% 0.234 to 5.538; p=0.567). The association between prematurity and LBW is highly significant (OR 49.224; CI 95% 15.470 to 156.621; p<0.001).).Conclusion: Primigravid women aged ≥35 years have higher proportions of maternal diseases. Despite being statistically insignificant, AMA has higher odds for LBW. Prematurity is highly asso¬ciated with LBW. Further research concerning high-risk maternal age needs to be done to improve women’s and children’s health. Keywords: advanced maternal age, primigravida, low birth weight. Correspondence:Ana Lucia Ekowati. Department Of Medical Biology, School of Medicine and Health Sciences, Atma Jaya Catholic University of Indonesia, Jakarta, Indonesia. Jl. Pluit Selatan Raya No.19, Jakarta, 14440. Email: ana.lucia@atmajaya.ac.id.